Milk-based supplementation in wet and dry feed forms: effects on growth performance, histomorphology, survivability, and economic outcomes in goslings - Iflazoglu Mutlu, Seda; Tatli Seven, Pinar; Simsek, Ulku Gulcihan; Erisir, Zeki; Baykalir, Yasin; Yalcin, Mehmet Hanifi; Mutlu, Muhsin (Springer, 2025)
This study investigated the effects of supplementing starter diets for goslings with milk powder (MP), milk replacer (MR), and whey powder (WP) in two different forms (dry and wet) on growth performance, survivability, intestinal histomorphology, and economic evaluation. Early nutrition is critical in goslings, yet limited research has addressed how milk-based supplements influence gut development and economic outcomes in this species. Therefore, a total of 192 one-day-old goslings were randomly assigned to eight groups in a 2 x 4 factorial experimental design involving two feed forms (dry, wet) and four additive treatments (0%, MP-4%, MR-4%, and WP-4%). The experiment lasted 70 days. Feed form significantly affected the feed conversion ratio, with better efficiency in the dry group (P < 0.001), while body weight, body weight gain, and feed intake were not significantly influenced by either feed form or additive (P > 0.05). Villus length, villus width, and crypt depth were greater in the dry feed groups, whereas lamina muscularis thickness was higher in the wet groups (P < 0.001). Among the additives, the WP groups had the highest villus length and lamina muscularis thickness, and the MR groups showed the highest villus width and crypt depth values (P < 0.001). The most favorable economic outcome was observed in the Dry-WP group, which had the lowest carcass cost at 16.00 TL per kg, compared to TL18.63 TL in the highest-cost group (Wet-MR). Goslings in all supplemented groups (dry-MR, dry-WP, wet-MP, wet-MR, and wet-WP) exhibited a 100% survival rate throughout the trial, while slightly lower survival (95.83%) was recorded in the control groups (P > 0.05). In conclusion, although milk-based supplementation did not significantly affect overall performance, it enhanced gut morphology and survivability. These findings suggest that WP, especially in dry form, may facilitate gastrointestinal development, enhance nutrient absorption and improve economic efficiency during the critical first three weeks of the early growth phase in goslings.
Keywords: Geese; Wet-dry feed; Performance; Survivability; Histomorphology; Economic evaluation